A cross-sectional study on the association between executive functions and social disabilities in people with a psychotic disorder - B.C. van Aken; R. Rietveld; A.I. Wierdsma; Y. Voskes; G.H.M. Pijnenborg; J. van Weeghel; C.L. Mulder (Schizophrenia Research: Cognition)
Background: Social recovery (SR) in people with psychotic disorders involves taking on social roles and completing daily tasks. Functional recovery (FR), particularly executive functions, is critical for these roles. Psychotic disorder patients often experience severe cognitive impairments, especially in executive functions. This study investigates the relationship between functional and social recovery in individuals with psychotic disorders and examines the effect of employment status on this association. Method: This cross-sectional study involved people with a psychotic disorder. SR was measured using the WHO-DAS, divided into Daily Functioning (DF) and Social Functioning (SF) scales. FR was measured using the BRIEF-A and the TOL. Employment status was categorized into Non-active, Otherwise Active, and Active. The Likelihood-ratio Test (LRT) was used for model selection. Results: Data from 251 participants (mean age 41.5) showed that the BRIEF-A affected both DF and SF, while the TOL only affected DF. Only being Otherwise Active influenced DF. Employment status had no influence on SF. Being Otherwise Active positively influenced perceived disabilities in Daily Functioning. Conclusion: Measuring executive functions using both performance-based and self-report measures is important. Both measures are associated differently with perceived disabilities in daily and social functioning. Being a volunteer or looking for a job positively influences perceived disabilities in Daily Functioning.